A retrospective record-based study to evaluate the profile of TB patients diagnosed and registered at DOTS center at the tertiary care center and to study the gaps in the implementation of the latest guidelines toward TB elimination - Ruchi Arora Sachdeva; Sahil Singh; MK Sen (The Journal of Association of Chest Physicians)
Context: Tuberculosis (TB) has infected mankind since time immemorial. India has been a breeding ground for this disease due to high population density and lack of awareness and education in the population. It is thus very important to understand the profile of TB patients and to find out the various limitations in the functioning of the National Tuberculosis Elimination Programme in order to focus on strengthening the goal of TB elimination in India. Aim: To describe the demographic profile and clinical characteristics of TB patients enrolled at DOTS Centre between October 2018 and December 2022 at a tertiary care center in North India. Settings and Design: A retrospective record-based study. Materials and Methods: A retrospective record-based study was carried out involving a review of existing data in Nikshay-2, which was accessed from the DOTS center at a tertiary care center in North India. Statistical Analysis Used: The data entry was done in a Microsoft EXCEL spreadsheet and analyzed using the SPSS version 17. Results: Of the total 2689 patients, 1222 (45.4%) were diagnosed with pulmonary TB (PTB) and 1467 (54.6%) with extrapulmonary TB, with most common type of EPTB was lymph node TB in 750 (51.1%) patients. The most common comorbidity was diabetes mellitus in 154 (30.1%) patients. Diagnosis of PTB was made by sputum microscopy in 410 (33.5%), CBNAAT 712 (58.2%), chest X-ray 21 (1.7%), and CT chest in 79 (6.4%) patients. Diagnosis of extra-PTB was made by CBNAAT 145 (9.8%), CT and MRI 190 (12.9%), and by cytopathology in 1132 (77.1%) patients. Outcome of TB patients was cured in 1082 (40.2%), treatment completed 1300 (48.3%), 32 (1.2%) patients died during treatment, 190 (7.1%) lost to follow-up, 2 patient migrated, treatment failed in 5 patients, regimen changed in 6 patients and data were not updated for 41 (1.5%) patients. Conclusion: This study thrusts on intensification of strategies like to improve lab infrastructure, to provide CBNAAT and LPA facilities at all medical colleges and district level, and IEC training to doctors (Interns, Medical officers, specialists), TB health workers and laboratory staff with the latest guidelines, importance of updating Nikshay portal and sensitization of treating physicians and lab personnel to send relevant samples for CBNAAT and LPA testing so as to detect drug-resistant cases on time in order to achieve elimination of disease.